Survey on testing technique for modern web application-rookies vantage point. (22nd August 2019) - Bharathi, M. Vijaya; Rodda, Sireesha
AJAX build 2.0 web applications depend in light of state full unique client and server correspondence and client side control of the DOM tree, which makes not the same as standard web applications. Provoking to more slip-ups and harder to set. Another methodology for this AJAX named ATUSA based web applications has been perceived for such accuses that can occur in any state and for making the test suite covering the ways. This approach called as ATUSA, realised by using a gadget which offers invariant checking of portions, module instrument. We portray this framework in three phases with six segments and furthermore accuse revealing limits, versatility, manual effort and level of motorisation testing. This paper mainly concentrates on rookie's vantage point of testing modern web application based on so far accomplished potential research done by software practitioners and experts.